SPD-Parteitag am 21.06.1981 in Wiesbaden Band 2;
Spur 1: (Fortsetzung von Band 1 Spur 1)<NZ>Fortsetzung der Rede Holger Börner<NZ>Aussparche - Strehlitz<NZ><NZ>1h41'45"-1h49'35" Heidemarie Wieczorek-Zeul; Bemerkungen: 1:1 Kopie